A spatial analysis of youth livelihoods and rural transformation in Ghana - Diao, Xinshen; Silver, Jed (International Food Policy Research Institute, 2017)
Ghana’s population is becoming younger and increasingly urbanized – by 2010, over half the population lived in urban settlements of more than 5,000 people – raising concerns among policy makers regarding the location and types of jobs required to employ the youth. The slow creation of for-mal urban jobs has particularly strong implications for young people entering the labor force: they are more educated than the older generation, with greater aspirations for non-farm employment and urban lifestyles (Anyidoho, Leavy, and Asenso-Okyere 2012). Without rapid industrialization to create more formal manufacturing and other non-agricultural jobs, youth in Ghana who leave the agricultural sector are increasingly likely to resort to informal services in both rural and urban areas. While much youth-related research has focused on changes in youth employment and livelihoods through rural-urban migration, a re-cent IFPRI Discussion Paper focuses on youth in the rural non-farm economy (Diao et al. 2017).